Nursing Students’ Knowledge Regarding the Management of Children with Poisoning: A Cross-Sectional Study: Pengetahuan Mahasiswa Keperawatan Mengenai Penatalaksanaan Anak dengan Keracunan: Sebuah Studi Cross-Sectional - Shreef, Noor Salah; Kadhim, Nuha Saeed; Khrabish, Nawras Talib (Indonesian Journal on Health Science and Medicine, 2024)
Background: Poisoning is a major public health concern, it is recorded as one cause of morbidity and mortality among children around the world, and its severity depends on the quantity and type of the poison substance. Objectives: Assessing Basrah nursing college students' understanding of how to care for children who have poisoning was the primary goal of the study. Methods: The study was carried out at the University of Basrah/College of Nursing between November 12, 2023, and March 18, 2024, using a descriptive cross-sectional design to accomplish its goal. Two hundred third- and fourth-year nursing students were chosen as a non-probability sample. The study's instrument, which includes sociodemographic information about nurses and a questionnaire to evaluate nursing students on child poisoning, was developed based on prior research on the topic. The SPSS software version 20 was used to analyze the data, which was gathered via a self-administered method. Results: The study shows, a majority (77.5%) of the total samples were female, (and 70%) of nursing students’ poor knowledge and management about poisoning in children. Conclusions: According to the study, Basrah University nursing students lacked a fundamental understanding of poisoning cases. The researchers' suggestion is to introduce poisoning in the curriculum and increase the education of programmers about poisoning and any acute cases. Highlights: Child poisoning is a global health concern with significant morbidity and mortality. Assess Basrah nursing students' knowledge of pediatric poisoning management. Students lack knowledge; curriculum enhancement and educational programs are recommended. Keywords: Assessment, Knowledge, Nursing Students, Poisoning